PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENTS TEAM ACHIEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR PS SISWA KELAS V SDN 010 SEMELINANG DARAT - Jamaluddin, Jamaluddin; Kurniaman, Otang; Witri, Gustimal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to improve students’ IPS learning achievement of grade fifth students of SDN 010 Semelinang Darat through the Application of STAD Cooperative Learning Model of STAD. This research is a classroom action research (PTK), which consists of two cycles. The subjects of the research are 20 students with 8 male students and 12 female students with heterogeneous capabilities. The research was conducted on 9thApril 2015 to 16thApril 2015. The data collection in this study was done by using the techniques of observation and tests. The observation sheet was analyzed by qualitative descriptive analysis, it aimed to describe the activities of teachers and students during the learning process, while the tests were analyzed by quantitative descriptive analysis of the achievement of the standard minimum score (KKM) of IPS and the average analysis of students’ IPS learning achievement aimed to know whether or not the improvement of students' IPS learning achievement. The results showed there is an improvement on students’ IPS learning achievement of the fifth grade srudents of Elementary School 010 Semelinang Darat. It can be seen from the number of students who completed the basic score that is 10 people or 50% increase in daily test I become 14 people or 70% and then increased in the second daily test to 16 people or 80%. The Improvement of student learning achievement also showed by an average of students' IPS learning achievement in basic score is 64.95 increased in the daily tests I became 72.1 then increased the daily test II became 79.75. From the research it can be concluded that the adoption of STAD Cooperative Learning Model to Improve Students’IPS Learning Achievement of the fifth grade students of Elementary School 010 Semelinang Darat 2014/2015.Keywords: Cooperative learning, STAD type, IPS Learning Achievement.